Death anxiety, self‐esteem, and health‐related quality of life among geriatric caregivers during the COVID‐19 pandemic. Issue 2 (19th January 2022) - Zhao, Xia; Zhang, Weihua; Su, Yonggang; Song, Yanping; Si, Huaxin; Zhu, Lifeng
Abstract: Background: The COVID‐19 pandemic has influenced all social spaces and older adults are susceptible to COVID‐19. Geriatric caregivers in nursing homes might experience death anxiety when faced with infected older adults and a closed working environment. Death anxiety is a negative and formidable affective state. Yet, little is currently known about the relationships among death anxiety, self‐esteem, and health‐related quality of life among geriatric caregivers during the COVID‐19 pandemic. This study aimed to examine whether self‐esteem could moderate the association between death anxiety and health‐related quality of life during the pandemic. Methods: A cross‐sectional study was conducted in Jinan and Heze cities, Shandong Province, from November 2020 to January 2021. Participants comprised a convenience sample of 236 geriatric caregivers in nursing homes. Data on sociodemographic variables, death anxiety, self‐esteem, and health‐related quality of life were collected. Descriptive analysis, Pearson correlation, and moderated analysis were used for statistical analysis. Results: Self‐esteem moderated the association between death anxiety and health‐related quality of life (death anxiety × self‐esteem: B = −0.113, 95% CI: −0.143, −0.018). Conclusion: This study revealed that self‐esteem played a moderating role between death anxiety and health‐related quality of life during the pandemic, which implies that mental health should be given more attention, and that interventions for improving self‐esteem need to be carried out.